The impact of substance use disorder on the mental health among COVID-19 patients: A protocol for systematic review and meta-analysis. Issue 46 (13th November 2020) - Kim, Yun Jin; Qian, Linchao; Aslam, Muhammad Shahzad
Abstract : Abstract: Substance use disorder (SUD) is associated with a high risk of physical and mental illness such as anxiety, depression, personality disorders, eating disorders, and abnormal mood changes. During the pandemic, SUD, a significant problem related to Coronavirus disease 2019 (COVID-19), is affecting adolescents. The recent available literature also emphasizes understanding the relationship between mental illness and SUD. Hence, it is essential to evaluate the scientific approach and examine the presented findings of articles published on SUD during the COVID-19 pandemic. A systematic review will be conducted using PubMed, PubMed Central, and Scopus bibliographic databases. The grey literature on the impact of SUD on mental health during the COVID-19 pandemic among adolescents will be identified using scholar google. The dependability and credibility of the findings will be examined using the ConQual approach. The methodologies of the included studies will be compared using ROBIS (risk of bias in systematic reviews tool), a measurement tool to assess systematic reviews (AMSTAR), and the JBI critical appraisal tool. The systematic review will be carried out on published articles, so it is exempt from ethics approval. The Center for Open Science (OSF) will be used as a data repository during the preparation of the protocol and completion of the systematic review. The research findings will be published in a related peer-reviewed journal.